Non-medical risk assessment of COVID-19 in parts of Central and East Java, Indonesia - Saputra, Aditya; Setiawan, Wisnu; Arif, Muhammad; Sriyono, Sriyono; Nurmalasari, Intan Rohmah; Dijaya, Rohman; Ulinuha, Agus (Quaestiones Geographicae, 2022)
The impact of the Coronavirus disease 2019 (COVID-19) pandemic varies as each country has a different capacity to stop the virus transmission and apply social distancing. A densely populated country, such as Indonesia, tends to face challenges in implementing social distancing due to population characteristics. The Indonesian government focuses on the medical aspect as this virus is new and has been deadly with a high transmission rate. Meanwhile, the non-medical risk during the pandemic is still unclear. The main objective of this study is to assess the non-medical risk at the village level in two agglomeration cities of Central Java: Greater Surakarta and Surabaya. The methodologies use a risk index, derived from the risk reduction concept. The hazard refers to the death toll, while the vulnerability relates to parameters such as disaster, social and public facilities, health facilities, economics and demography. Further, the parameters were weighted based on expert judgement derived using analytical hierarchy process (AHP). The study found that the disaster aspect had the highest weight (0.38), followed by health facilities (0.31), economics (0.17), social-public facilities (0.11) and demography (0.04). The standard deviations of those parameters were relatively low, between 0.12 and 0.25. A low vulnerability index (0.05–0.36) was observed to be dominant in both study areas. There are 11 villages in Greater Surakarta and 30 villages in Greater Surabaya with high vulnerability index. Disaster-prone areas, low economic growth, lack of health facilities and aged demographic structure significantly added to this vulnerability. Further, a high-risk index (0.67–1.00) is observed in three villages in Greater Surabaya and one village in Greater Surakarta. These villages are relatively close to the city centre and have good accessibility. Furthermore, these four villages experienced the severest impact of the pandemic because the furniture and tourism sectors were their primary industries.